2012
DOI: 10.2500/ajra.2012.26.3733
|View full text |Cite
|
Sign up to set email alerts
|

Crenotherapy Modulates the Expression of Proinflammatory Cytokines and Immunoregulatory Peptides in Nasal Secretions of Children with Chronic Rhinosinusitis

Abstract: Crenotherapy induced a down-regulation of nasal mucosal inflammatory mediators in children with CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
(37 reference statements)
2
26
0
1
Order By: Relevance
“…Many ENT disorders are widely treated by crenotherapy, including respiratory infections (13). Recurrent respiratory infections represent a relatively common problem in childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ENT disorders are widely treated by crenotherapy, including respiratory infections (13). Recurrent respiratory infections represent a relatively common problem in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was recently reported that crenotherapy with sulfate-sodium-chloride water modulated the expression of proinflammatory cytokines and immunoregulatory and antimicrobial peptides (such as TNF-a, human~-defensin 2, and calprotectin) in nasal secretions of children with chronic rhinosinusitis (13). In fact, a 15-day course of this thermal water inhalation by aerosol reduced these biomarkers as well as nasal symptoms and quality of life.…”
mentioning
confidence: 99%
“…Apparently, crenotherapy acts as an antiinflammatory, a mucolytic, and a mucus and trophic regulator, thereby boosting the body's immune defenses (7)(8)(9)(10)(11). In particular, it induces vasodilatation and capillary permeability, stimulates the synthesis of IgAs, and reduces serum and tissue levels of IgE, thereby improving mucociliary clearance (7)(8)(9)(10)(11). Notwithstanding these results, the efficacy of crenotherapy in the treatment of CRS still remains unclear.…”
Section: Receivedaugust 302014 -Accepted October 21 2014mentioning
confidence: 99%
“…The use of these waters for prophylactic and therapeutic purposes is called spa treatment and the curative effect stems from the heat of the water as well as its mineral content (Karagülle and Karagülle, 2000;Vaccarezza and Vitale, 2010). A recent study showed that in children with chronic rhinosinusitis a15 minute/15 day inhalation of thermal water containing sulfate, sodium and chloride results in the reduction nasal mucosal inflammatory mediators (Passariello et al, 2012). Yet other studies show that many mineral waters, especially those rich in bicarbonate, have an effect on lipoprotein levels and that their consumption causes a reduction in total serum cholesterol and LDL cholesterol levels (Schoppen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%